Communication channel optimization in MIMO system - Кузнецов, А.А.; Цопа, А.И. (Radiotekhnika, 2012)
Technique for digital MIMO communication system design using optimization algorithms is reviewed. Results of some optimization algorithms computing are shown. Imitational communication system model is used for the fitness function calculation. Investigations are based on experimental measurements and the simulated system parameters approach the requirements of IEEE 802.11n standard.